A Thirst for Change : The World Bank Group’s Support for Water Supply and Sanitation, with Focus on the Poor - Independent Evaluation Group (World Bank, Washington, DC, 2018)
This evaluation assesses the World Bank Group’s effectiveness in supporting improved access to adequate, reliable, and sustained water and sanitation services in client countries. It also examines how well the Bank Group is equipped to support the countries in moving toward sustained water and sanitation services for all, with a focus on the poor, in keeping with Sustainable Development Goal 6. The World Bank Group provided $30.3 billion for WSS to client countries during FY2007-16. The World Bank accounted for the largest share with $28.4 billion (93 percent), followed by the International Finance Corporation (IFC) with $1.5 billion (5 percent), and the Multilateral Investment Guarantee Agency (MIGA) with $0.4 billion (2 percent). Lack of financial viability and accountability of service providers are at the core of gaps and disparities in global water and sanitation services, and the World Bank Group’s response has been inadequate. Securing financial viability and institutional accountability is also crucial to attract much needed investments into the water and sanitation service sector, including private sector finance. The water and sanitation services sector faces cross-sectoral challenges that are approaching crisis proportions in many areas, but the World Bank Group has not developed yet a systematic response to address such challenges. Without tackling financial viability and cross-sectoral impacts head-on, credible progress towards SDG 6 is unlikely. IEG’s evaluation also highlights pioneering and successful initiatives by the Bank in the WSS sector in several countries. The challenge is to replicate these positive experiences elsewhere.